(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Sport is considered as a cultural phenomenon and sphere of public life, its value potential, sociocultural characteristics as factors in the development of a person’s sports culture, the importance of physical culture and sports activities for the formation of a person in the education system.